2019
DOI: 10.1016/j.sjbs.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α lipoic acid on noise induced oxidative stress in rats

Abstract: This study was conducted to identify how exposure to ambient noise that is over 75 dB affects the oxidant-antioxidant profile using hematological and biochemical indicators, and to investigate the effects of a strong and current antioxidant, lipoic acid, on rats that were subjected to noise stress. For this purpose, five groups of eight rats were formed as follows: Control (K), Noise Exposure (GK), Lipoic Acid (LA), Noise Pollution + Lipoic Acid (GK + LA) and Oil (Y). The blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…However, groups supplemented with vitamin C during chronic variable stress exposure showed no significant increase in MDA. Karafakioğlu [25] reported increased levels of MDA in noise only model of stress exposure with lipoic antioxidant supplementation reducing the MDA activity. Similarly, oxidative stress induced by hypoxia in animals was reported to significantly increase MDA activity with selenium supplementation significantly decreasing MDA tissue and plasma activity [26].…”
Section: Oxidative Biomarkers Activitymentioning
confidence: 99%
“…However, groups supplemented with vitamin C during chronic variable stress exposure showed no significant increase in MDA. Karafakioğlu [25] reported increased levels of MDA in noise only model of stress exposure with lipoic antioxidant supplementation reducing the MDA activity. Similarly, oxidative stress induced by hypoxia in animals was reported to significantly increase MDA activity with selenium supplementation significantly decreasing MDA tissue and plasma activity [26].…”
Section: Oxidative Biomarkers Activitymentioning
confidence: 99%
“…As a stressor, noise can induce oxidative stress in the body and regulate the nervous system, circulatory system and endocrine system. It is known that some antioxidants, such as lipoic acid ( 36 , 37 ) and Scoparia dulcis ( 38 ) can reduce changes in humoral and cellular immunity caused by noise. Therefore, we speculate that the influence of noise on the immune system may be correlated with neuroendocrine regulation and oxidative stress, although its specific mechanism remains to be explored.…”
Section: Mechanisms By Which Noise Causes Immune System Disordersmentioning
confidence: 99%
“…The result indicated the role of antioxidant, anti-stressor and immune stimulant activity of SD. Furthermore, other antioxidants also show similar therapeutic effects against noise such as vitamins A or E (tocopherols) and α lipoic acid ( 36 ).…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…In the both human and animal experiments, it was noted that exposure to noise increases peroxidation of lipids and alters the antioxidant enzyme levels 26 . In an animal study, it was also found that the oxidative stress indicator increased as a result of exposure to a noisy environment 27 . Supporting to these evidences, we observed a significant increase in the oxidative stress level in the rats exposed to the rock music.…”
Section: Discussionmentioning
confidence: 99%